2019
DOI: 10.1101/538108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting educational achievement from genomic measures and socioeconomic status

Abstract: The two best predictors of children’s educational achievement available from birth are parents’ socioeconomic status (SES) and, recently, children’s inherited DNA differences that can be aggregated in genome-wide polygenic scores (GPS). Here we chart for the first time the developmental interplay between these two predictors of educational achievement at ages 7, 11, 14 and 16 in a sample of almost 5,000 UK school children. We show that the prediction of educational achievement from both GPS and SES increases s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 25 publications
3
50
1
Order By: Relevance
“…First, we studied the association of EA-PGS with school performance in the full sample and compared the results to those from previous studies. 8,9 In our sample, the maximum variance explained in school performance by EA-PGS was 8.4%. This was lower compared to the estimates reported in previous studies 8,9 (R 2 =14%).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…First, we studied the association of EA-PGS with school performance in the full sample and compared the results to those from previous studies. 8,9 In our sample, the maximum variance explained in school performance by EA-PGS was 8.4%. This was lower compared to the estimates reported in previous studies 8,9 (R 2 =14%).…”
Section: Discussionmentioning
confidence: 65%
“…Most of the previous studies on the association of EA-PGS with EA or school performance were based on individuals from the general population. [7][8][9] It was therefore not clear if results from such studies could be generalized to those with psychiatric disorders. Nation-wide register based cohorts such as iPSYCH 25 are well suited to address such research questions as they offer a unique opportunity to study both the genetic and environmental factors of multiple psychiatric disorders at the same time within a single population setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If this result reflects a true effect, it could represent a catch-up -subjects with lower WM show greater gains in WM during adolescence. However, a previous study of PGS and SES on IQ showed a widening gap between subjects with low and high EduYears-PGS 45 . At least in part, our results here could alternatively be explained by ceiling effects, which could artificially lead to high performing subjects having less room to improve.…”
Section: Adolescent Developmentmentioning
confidence: 69%